Exploring the role of serum adiponectin and its holigomerization in fibrotic interstitial lung diseases: results from a cross-sectional study - Ersilia Nigro; Vito D’Agnano; Raffaella Pagliaro; Marta Mallardo; Andrea Bianco; Carmine Picone; Adolfo Gallipoli D’Errico; Aurora Daniele; Fabio Perrotta (BMC Pulmonary Medicine)
Abstract Intestitial lung diseases (ILDs) include a group of inflammatory and fibrotic pulmonary disorders with different etiologies which in several patients might lead to a progressive reduction of respiratory capacities and chronic respiratory failure. Nowadays, biomarkers for predicting the ILD progression and response to therapies are lacking. Adiponectin, the most abundant peptide secreted by adipocytes, has emerged as a potential response biomarker in fibrotic progressive ILDs. The aim of this observational prospective single-center cross-sectional study is therefore to verify whether serum adiponectin levels were altered in patients with fibrotic ILDs (f-ILDs) and its correlation with clinical and pulmonary function data. Sixty-four f-ILDs patients – divided in three subgroups IPF, CTD-ILDs and other f-ILDs - and 45 healthy subjects were recruited. Serum adiponectin concentration were measured by enzyme-linked immunosorbent assay (ELISA). Pulmonary function tests and clinical data were systematically collected. The results showed that patients with f-ILDs have reduced circulating levels of serum adiponectin (12.5 [10.8–15.4] versus 19.3 [17.3–20.8] p < 0.001). No significant difference in adiponectin levels were observed in the different f-ILDs subgroups (p = 0.619). Adiponectin levels were not associated with progression of f-ILDs (p = 0.745). High molecular weight adiponectin isoform was highly reduced in patients with f-ILDs. In patients with CTD-ILDs – but not in other subgroups – adiponectin levels were associated with pulmonary function and GAP index. These resuls support a potential role of adiponectin as diagnostic and prognostic biomarker of f-ILDs.